Psychometric Properties of the Problems Assessment for Substance Using Psychiatric Patients - Sayed Hadi Sayed Alitabar; Maryam Falahatpisheh; Mojtaba Habibi Asgarabad; Musa Arvin; Ali Sarvestani (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Today, substance use problem is an important and critical problem in the world. This study investigates the psychometric properties of the Problems Assessment for Substance Using Psychiatric Patients (PASUPP). Materials and Methods: Research was descriptive and correlational. The study population consisted of all psychiatry patients with drug addiction in Tehran. The sample consisted of 381 patients (143 women and 238 men) were selected with a multi-stage cluster sampling of areas from drug rehabilitation centers in Tehran. The PASUPP, Drug Abuse Screening Test (DAST) and Relapse Prediction Scale (RPS) were used as instrument. In order to assess the first order confirmatory factor, the weighted lowest squares (WLS) and to assess the adequacy of the model to the data, the parameters of RMR, RMSEA, CFI, AGFI, GFI, c2، c2/ df & Dc2 were used. Results: The PASUPP was confirmed after the first time factor structure of using confirmatory factor analysis. The PASUPP had a good internal consistency (Cranach's alpha, and the reliability of the test within a week, 88/0, 76/0). Also this scale had a positive correlation with Drug Abuse Screening Test and Relapse Prediction Scale which indicates its convergent validity. Conclusion: The overall results showed that the Problems Assessment for Substance Using Psychiatric Patients in Iranian society is valid. It can be said that self-report scale tool is useful for research purposes and addiction.